2021
DOI: 10.1093/ageing/afab163
|View full text |Cite
|
Sign up to set email alerts
|

Acute sarcopenia changes following hospitalization: influence of pre-admission care dependency level

Abstract: Introduction Hospitalization is associated with acute changes in sarcopenia status in older people, but the influencing factors are not fully understood. Pre-admission care dependency level as a risk factor has not yet been investigated. Objective Evaluate if pre-admission care dependency level is an independent predictor of sarcopenia changes following hospitalization. Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Ageing produces changes in body composition [ 32 ], and sarcopenia increases with age [ 33 ], which could be another reason for the high rate of sarcopenia in our study, as previously demonstrated by other authors [ 34 ]. However, the degree of sarcopenia may be influenced by various risk factors, such as age, a prolonged hospital stay > 7 days, the need for invasive mechanical ventilation, and obesity [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…Ageing produces changes in body composition [ 32 ], and sarcopenia increases with age [ 33 ], which could be another reason for the high rate of sarcopenia in our study, as previously demonstrated by other authors [ 34 ]. However, the degree of sarcopenia may be influenced by various risk factors, such as age, a prolonged hospital stay > 7 days, the need for invasive mechanical ventilation, and obesity [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…The relationship between sarcopenia and COVID-19 has received substantial interest in the current literature. Hospitalization has been confirmed to be associated with acute changes in sarcopenia status in older people ( 20 , 21 ). Studies of hospitalized patients have described biochemical evidence of muscle damage ( 22 ) during the pandemic, and it has been speculated that patients with COVID-19 are at increased risk of acute sarcopenia ( 23 , 24 ), which is characterized by low skeletal muscle mass (LSMM) and reduced strength.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital transfers are stressful for nursing home residents and their families, increase care costs, and lead to unintended consequences such as nosocomial infections, as well as cognitive and functional decline [1][2][3][4] . Compared to older adults living in the community, nursing home residents experience more hospital transfers.…”
Section: Introductionmentioning
confidence: 99%